2019
DOI: 10.1029/2019gl082736
|View full text |Cite
|
Sign up to set email alerts
|

Urban Expansion and Drying Climate in an Urban Agglomeration of East China

Abstract: Urban land expansion is one of the most conspicuous aspects of urbanization and has profound impacts on regional climate change. Most studies, however, focus on its impacts on surface temperature, and possible effects on atmospheric humidity are less known. By examining the humidity changes in the Yangtze River Delta urban agglomeration of China during 1961–2014, we find a prominent urban dry island (UDI) effect in this urban agglomeration, as characterized by reduced humidity and increased vapor pressure defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 73 publications
(127 reference statements)
8
88
0
Order By: Relevance
“…vapour pressure and specific humidity) at any given point in time. Similar findings have been observed in regard to spatial variation in temperature (Cavan et al 2014;Feyisa et al 2014), humidity (Adebayo 1991;Yang et al 2017;Hao et al 2018;Luo and Lau 2019) and heat index (Hass et al 2016;Scott et al 2017). Materials such as concrete and asphalt and the presence of buildings promote the transformation of shortwave radiation into heat and its retention (Landsberg 1981;Oke 1987).…”
Section: Discussionsupporting
confidence: 78%
“…vapour pressure and specific humidity) at any given point in time. Similar findings have been observed in regard to spatial variation in temperature (Cavan et al 2014;Feyisa et al 2014), humidity (Adebayo 1991;Yang et al 2017;Hao et al 2018;Luo and Lau 2019) and heat index (Hass et al 2016;Scott et al 2017). Materials such as concrete and asphalt and the presence of buildings promote the transformation of shortwave radiation into heat and its retention (Landsberg 1981;Oke 1987).…”
Section: Discussionsupporting
confidence: 78%
“…The RH under heat waves were lower than that under normal conditions for most hours in all three cities. This phenomenon is also called the urban dry island, which can be intensified by urban expansion as well (Hao et al, ; Luo & Lau, ; Yang, Ren, et al, ). The RH in Shanghai was higher than that in Beijing and Guangzhou, which could explain the highest AT in Shanghai.…”
Section: Resultsmentioning
confidence: 99%
“…Our result was consistent with Chen et al (2019) and Wang et al (2020) who concluded that the cropland greening in China and the Loess Plateau was mainly caused by human land‐use management practices such as multiple cropping and heavy fertilizer usage. Urbanization and urban expansion, on the one hand, generally occurred at the expense of grassland or cropland, which directly related to the decrease in vegetation covers and ET of the land surface, thereby reducing atmospheric humidity and elevating vapor pressure deficit in urban core areas (Hao et al, 2018; Lin et al, 2020; Luo & Lau, 2019). However, the growth of urban areas only accounted for a small fraction of land changes in the Loess Plateau.…”
Section: Discussionmentioning
confidence: 99%